Recircumscription of Delphinium subg. Delphinium (Ranunculaceae) and implications for its biogeography. Issue 3 (23rd June 2017) - Xiang, Kun-Li; Aytaç, Zeki; Liu, Yang; Espinosa, Felipe; Jabbour, Florian; Byng, James W.; Zhang, Cai-Fei; Erst, Andrey S.; Wang, Wei
Abstract: The monophyly of Delphinium subg. Delphinium remains unresolved, owing to the controversial systematic position of the monotypic, eastern Asian endemic D. sect. Anthriscifolium. The other section of the subgenus, D. sect. Delphinium, is distributed in the Irano‐Turanian (IT) region extending westward to the Mediterranean Basin. Recently, a new genus endemic to Turkey, Pseudodelphinium, was described and considered related with Delphinium (Delphinieae) or Garidella (Nigelleae). In this study, we first conducted a broad phylogenetic analysis within Ranunculaceae using matK sequences and placed Pseudodelphinium in Delphinieae. We then performed a series of analyses using four molecular markers (trnK‐matK, trnS‐G, trnL‐F, ITS) focused on the tribe. The phylogenetic analyses based on the four‐marker dataset indicate that Pseudodelphinium is embedded within sect. Delphinium. The Swofford‐Olsen‐Waddell‐Hillis tests also reject the exclusion of Pseudodelphinium from Delphinium and sect. Delphinium. The monophyly of subg. Delphinium is not recognized because sect. Anthriscifolium unites with D. subg. Delphinastrum and Consolida. Based on molecular, morphological, and karyological data, we raise sect. Anthriscifolium to subgeneric status, whereas sect. Delphinium composed subg. Delphinium s.str. An integration of phylogenetic, molecular dating, and biogeographical methods indicates that the subgenus s.str. originated in East Asia during the latest Oligocene and began to diversify in the IT region at 8.45 Ma. Subsequently, the westward colonization events occurred at 7.06 Ma from the IT region to the Italian and Balkan Peninsulas and at 5.4 Ma from Italy to North Africa. A dispersal from North Africa to the Iberian Peninsula was inferred in the late Pliocene, supporting a hypothesis of trans‐sea dispersal. Within the Mediterranean Basin, climate aridification and eustatic sea‐level changes could have initiated the westward stepwise expansion of Delphinium.